Atomically Dispersed Pd, Ni, and Pt Species in Ceria-Based Catalysts: Principal Differences in Stability and Reactivity - Neitzel, Armin; Figueroba, Alberto; Lykhach, Yaroslava; Skala, Tomas; Vorokhta, Mykhailo; Tsud, Nataliya; Mehl, Sascha; Sevcikova, Klara; Prince, Kevin C.; Neyman, Konstantin M.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2016)
We have investigated the stability and the reactivity of atomically dispersed Pt, Pd, and Ni species on nanostructured CeO2 films by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy in combination with density functional calculations. All three metals reveal specific similarities associated with the high adsorption energy of atomically dispersed Pt2+, Pd2+, and Ni2+ species that exceeds the corresponding cohesive energies of the bulk metals. The corresponding Pt-CeO2, Pd-CeO2, and Ni-CeO2 model catalysts have been prepared in the form of thin films on CeO2(111)/Cu(111) substrates and investigated experimentally under ultrahigh vacuum conditions. The atomically dispersed Pt2+, Pd2+, and Ni-2 species were formed exclusively at low concentrations of the corresponding metals. High concentrations resulted in the presence of additional metal oxide phases and emergence of metallic particles. We found that under the employed experimental conditions the Pd-CeO2 films closely resemble the Pt-CeO2 system with respect to the redox behavior upon reaction with hydrogen. Unlike Pt-CeO2, the Pd-CeO2 system shows a strong tendency to stabilize Pd2+ not only at the surface but also in the ceria bulk. In sharp contrast to both Pt-CeO2 and Pd-CeO2, the Ni-CeO2 system does not exhibit the redox functionality required for hydrogen activation due to the remarkably high stability of Ni2+ species.